Association of Polypharmacy and Statin New-User Adherence in a Veterans Health Administration Population: A Retrospective Cohort Study. (October 2013) - Watanabe, Jonathan H.; Bounthavong, Mark; Chen, Timothy; Ney, John P.
Background: The relationship between multiple medication consumption and medication adherence is not well understood. Objective: To determine the association between the number of active medications on the patient medication profile at baseline and adherence in new users of statins.Methods: This was a retrospective cohort study of new users of statin medications from the Veterans Health Administration. We explored the correlation between the number of baseline medications and adherence, grouping patients by number of active medications on the study index date via Cochran-Armitage trend test and multiple linear regression. The adherence metric calculated for each patient was the medication possession ratio (MPR). Adherence was defined as achieving a 0.8 MPR or greater in primary analysis and a 0.9 MPR or greater in the secondary analysis.Results: There was a statistically significant trend of increasing proportion of adherent participants as baseline medication count grew (P value < .001). The regression further demonstrated that statin MPR was increased by 0.04, 0.07, 0.10, and 0.14 for the 6 to 10 medication count, 11 to 15 medication count, 16 to 20 medication count, and >20 medication count groups, respectively, in comparison with the reference 1 to 5 medication count group (P < .001 for all comparisons). An MPR threshold of 0.9 provided consistent evidence of improved adherence as number of medications increased (P < .001).Conclusions: Increased medication count at baseline was associated with improved adherence for new users of statins.